Differences In ESG Values Between Indonesia And Singapore - Fadilla, Fadilla; Adam, Mohammad; Isnurhadi, Isnurhadi; Yuliani, Yuliani (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2025)
This study attempts to prove whether there is a difference between the ESG (Environmental , Social and Governance) Score values of companies that have gone public in Singapore and Indonesia. To prove this, we tested it with a Statistical analysis, namely the Difference Test in statistical terms, the Paired t-test. If the Significance value is less than 0.05, there is a difference, otherwise there is no difference. The result of the difference test in this study is 0.00, which means there is a difference between the ESG scores of Indonesia and Singapore.